Outcomes following intradetrusor onabotulinumtoxinA in a national cohort of nursing home residents - Leo D. Dreyfuss; Farnoosh Nik‐Ahd; Lufan Wang; Abigail Shatkin‐Margolis; Kenneth Covinsky; W. John Boscardin; Anne M. Suskind (BJUI Compass)
Abstract Objectives To determine predictors of treatment success and complications following intradetrusor onabotulinumtoxinA injections among a large cohort of nursing home (NH) residents, representing one of the most frail and vulnerable populations in the United States. Materials and methods This is a retrospective cohort study of long‐stay NH residents who underwent onabotulinumtoxinA injections between 2014 and 2016. Residents were identified using the Minimum Data Set (MDS) linked to Medicare claims. Frailty was measured using the Claims‐based Frailty Index and socioeconomic status using the Area Deprivation Index (ADI; higher ADI = increasing social deprivation). The primary outcome was treatment success, defined as repeat onabotulinumtoxinA injection within 1 year of index injection. Secondary outcomes included 30‐day complications and urinary retention, defined as new indwelling urinary catheters identified on the MDS at 3 months. Results OnabotulinumtoxinA injections were performed in 1683 NH residents. Mean age was 78.2 years, 74% were female and 22.8% had an indwelling urinary catheter at baseline. A total of 38.4% of residents had ≥1 30‐day complication and 14.6% had a new catheter at 3 months. Repeat injections were performed in 34.3% of residents within 1 year. Repeat injections were more likely among residents who were female [adjusted relative risk (aRR) 1.29; 95% CI 1.08–1.54] and who had a baseline catheter (aRR 1.30; 95% CI 1.11–1.52). Residents who were ≥85 years (aRR 0.78; 95% CI 0.64–0.96) and those in the lowest quartile ADI (aRR 0.75; 95% CI 0.61–0.93) were less likely to undergo repeat injections. Conclusion Among this population of NH residents, who are by definition frail and comorbid, rates of repeat onabotulinumtoxinA injections are comparable to retrospective analyses of younger adults and independent of frailty and comorbidity. Based on these findings, surgeons should consider the entire clinical picture when evaluating patients for onabotulinumtoxinA injections and should not necessarily exclude those who are frail or comorbid from this potentially quality‐of‐life‐improving therapy.